In vitro interactions between Trichoderma harzianum and pathogenic fungi damaging horse-chestnut (Aesculus hippocastanum) leaves and fruits - Pastirčáková, Katarína (Biological Letters, 2019)
Interactions between 3 pathogenic fungi damaging horse-chestnut (Aesculus hippocastanum) leaves and fruits – Phyllosticta sphaeropsoidea, Phomopsis carposchiza, and Diaporthe padi – and the antagonistic fungus Trichoderma harzianum were studied to determine their mutual influence in vitro. Antibiosis of colonies developing on 5 nutrient media was tested. The 3 studied T. harzianum isolates differed in their antagonistic potential. although T. harzianum isolates significantly inhibited the growth of Phomopsis carposchiza, the mycelium growth of some of the re-isolates on fresh medium indicates an inadequate antagonistic effect of T. harzianum on this species. The tested Trichoderma isolates showed stronger antagonism towards the other pathogens, reflected in overgrowing of Phyllosticta sphaeropso-idea and Diaporthe padi and reducing their growth. Granulation of the cytoplasm and lysis of hyphae of the fungal pathogens were the most frequently observed effects of the interaction.